PRESSURE DROP IN A SPOUTED BED OF CORK STOPPERS - Magalhães, A.; Pinho, C. (Revista de Engenharia Térmica, 2006)
The spouted bed is a particular type of fluidized bed which is well suited for the handling of large size particles like cork stoppers. It is commonly used for the drying of granulates and the present work is the first part of a study concerning the drying of cork stoppers in a laboratory scale spouted bed reactor. The study considers two stoppers size, one the port wine stopper and another small size stopper. The choice of these smaller sizes was imposed by the small dimensions of the reactor. In this preliminary set of experiments the fluid-dynamics regime of the particular two phase flow was characterized. For different experimental situations covering several air flows and temperatures typical of cork drying operations the evolution of pressure drop was evaluated and a correlation for the minimum spouting velocity was obtained.